The Political Economy of Trauma: International Humanitarian Law, the Commercialization of Mental Health, and the Unaccounted Casualties of Nigeria’s Counter-Insurgency - Eni Eja Alobo; Egbe Inyang John; Wekekayo Eteng Ekpe; Aji Elemi Eko; Eko Thomas Alobo (dialektika kontemporer, 2026)
This paper proposes a transformative integration of Ubuntu philosophy, captured in the phrase Umuntu ngumuntu ngabantu meaning